Molecular and serological evaluation of Toxoplasma gondii among female university students in Mamasani district, Fars province, southern Iran - Mohsen Kalantari; Qasem Asgari; Khadijeh Rostami; Shahrbano Naderi; Iraj Mohammadpour; Masoud Yousefi; Mohammad Hassan Davami; Kourosh Azizi (Shiraz University of Medical Sciences, 2020)
Background: Anti-Toxoplasma antibodies were identified in female university students referred to Valie-Asr hospital of Mamasani from Azad and Payame-Noor Universities, using serological and molecular methods. Methods: Based on the prevalence and characteristics method, 504 serum samples were collected from female university students, during 2015, and evaluated by Enzyme-Linked Immun-Sorbent Assay (ELISA), Modified Agglutination Test (MAT), and Polymerase Chain Reaction (PCR) based on B1 gene for detection of Toxoplasma gondii. The data were analyzed using SPSS 19 software. Results: Out of 504 studied female students, 27 (5.36%) and 36 (7.14%)  cases were found to be positive for anti-Toxoplasma IgG antibodies by MAT and ELISA, respectively. Moreover, 5 (0.99%) cases were found to be positive for anti-Toxoplasma IgM. PCR detected the Toxoplasma DNA in 58 out of 504 (11.51%) samples. Conclusions: Findings of the current study revealed that Toxoplasma was a common infection among female university students in Mamasani district in Fars province. Seronegative individuals are at risk for the disease, as well as congenital toxoplasmosis in later stages of their life. Preventive measures should be taken to reduce the rate of infection.